Persepsi Masyarakat Terhadap Pendidikan Formal Kaitannya dengan Jumlah Anak-anak Putus Sekolah - Tubu, Bunga; Malik, Abd; Syarif, Erman (LaGeografia, 2021)
This study aims to determine : 1). Public perception of formal education in Takalar Village, Mappakasunggu Disrict, Takalar Regency. 2). Factors affecting school dropout in Takalar Village, Mappakasunggu Disrict, Takalar Regency. 3). The relationship between public perceptions of formal education with factor affecting children dropout school. The population in this study are people who have children age 7-18 years old but do not attend school. The number of population is this study is not known with certainly, so the sampling was carried out in a non random- way, namely by using the snowball sampling technique. The sampel in this study amounted to 36 people. This research ia a quantitative descriptive research. Data collaction technique include observasion, questionnaires and documentation. Data analysis was performed using descriptive analysis and Rank spearman correlation test. Based on the research results, the level of public perception in Takalar Village is still low, namely 58,3%. In general, the factor that cause children dropout of school in Takalar Village, Mappakasunggu Disrict, Takalar Regency are due the parents recent education, parents job, income, total dependents, parent motivation and interest in children learning. There is a significant relationship between the latest education work and income to the community’s perception of formal education.